Bioerosion and encrustation of the rocky shore dwellers along the Arabian Gulf, Northeast Saudi Arabia - Abdelbaset S. El-Sorogy; Hassan Alzahrani (Journal of King Saud University: Science, 2024)
The coastal area between Al-Khafji and Al-Jubail, Arabian Gulf, Saudi Arabia is characterized by natural and artificial rocky shores, which inhabited by intensive dwellers. The present work aimed to shed light on the taxonomy, distribution, and environmental factors affecting the abundance of the invertebrate borers and encrusters in the study area. A total of 614 specimens of bivalve, gastropod, coral, and lithified rocky shores were collected from 13 sites. Eighteen ichnospecies of 8 ichnogenera were identified and illustrated. These traces were produced by clionid sponges (31.75%), endolithic bivalves (26.19%), naticid gastropods (24.60%), polychaete annelids (15.08%), acrothoracican barnacles (1.85%), and vermitid gastropods (0.53). The rocky shore dwellers act as hard substrate for colonization by serpulids, barnacles, bryozoans, and other cemented invertebrates. Most of the thick invertebrates and lithified rocky grounds were bioeroded by endolithic bivalves, clionaid sponges, polychaete annelids, and acrothoracican barnacles, while the thin walled invertebrate dwellers were bioeroded by naticid gastropods and clionaid sponges. Barnacles, serpulid worms and some molluscs were intensively covered the rocky shore blocks and solid rubbish in intertidal area facing wave action to comb microscopic food from the water.